1975
DOI: 10.1042/bj1460213
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell membrane galactosyltransferase in concanavalin A agglutination of erythrocytes

Abstract: It has been previously observed that rabbit erythrocyte cell surface galactosyltransferase appears to play a role in concanavalin A agglutination of these erythrocytes (Podolsky et al., 1974). Further, a correlation between the occurrence or level of cell surface galactosyltransferase and concanavalin A agglutinability of other cell types has also been observed. The mechanism by which rabbit erythrocyte galactosyltransferase participates in concanavalin A agglutination has now been further defined. The enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In preliminary experiments, we have defined some requirements for galactose transfer in YC8 ascitic fluids and sera; the results we obtained are described [6] with normal human and cancerous sera.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary experiments, we have defined some requirements for galactose transfer in YC8 ascitic fluids and sera; the results we obtained are described [6] with normal human and cancerous sera.…”
Section: Resultsmentioning
confidence: 99%
“…Galactosyltransferase activities have been described in various biological fluids [1][2][3][4][5] and more recently in human cancer sera [6], but to our knowledge not yet in cancerous ascitic fluids. So we have undertaken to investigate the galactosyltransferase activity of ascitic fluids towards endogenous and exogenous acceptors, and comparatively i n sera from the Balb/c mouse strain bearing the ascitic transplantable isogenic tumor YC8, a lymphoma which possesses at least two tumor membrane antigens [7].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylamide gel electrophoresis of sera and detection of galactosyltransferase activity from slices of polyacrylamide gels were performed by the method of Podolsky and Weiser (9). It was observed that the cancer-associated cathodal peak of activity (isoenzyme II) could not be detected * To whom reprints should be addressed.…”
Section: Methodsmentioning
confidence: 99%
“…Galactosyltransferase activity has also been detected in rat and human serum as a soluble activity (6,7), but the total activity was not previously found to be elevated in cancer patients unless liver disease was also present (8). However, by means of discontinuous polyacrylamide gel electrophoresis Podolsky and Weiser were able to detect in cancer patients a slower moving peak of activity that separated well from the major, more anodally directed peak of activity found in all patients (9). The present report describes the cancer patients who were tested for serum galactosyltransferase isoenzymes, compares them with disease and normal controls, and examines possible clinical and laboratory correlations with serum levels of these isoenzymes.…”
mentioning
confidence: 95%
See 1 more Smart Citation